Long pentraxin 3 (PTX3) levels predict death, intubation and thrombotic events among hospitalized patients with COVID-19 - Lapadula, Giuseppe; Leone, Roberto; Bernasconi, Davide Paolo; Biondi, Andrea; Rossi, Emanuela; D’Angiò, Mariella; Bottazzi, Barbara; Bettini, Laura Rachele; Beretta, Ilaria; Garlanda, Cecilia; Valsecchi, Maria Grazia; Mantovani, Alberto; et al. (Frontiers in Immunology, 2022)
Background PTX3 is an important mediator of inflammation and innate immunity. We aimed at assessing its prognostic value in a large cohort of patients hospitalized with COVID-19. Methods Levels of PTX3 were measured in 152 patients hospitalized with COVID-19 at San Gerardo Hospital (Monza, Italy) since March 2020. Cox regression was used to identify predictors of time from admission to in-hospital death or mechanical ventilation. Crude incidences of death were compared between patients with PTX3 levels higher or lower than the best cut-off estimated with the Maximally Selected Rank Statistics Method. Results Upon admission, 22% of the patients required no oxygen, 46% low-flow oxygen, 30% high-flow nasal cannula or CPAP-helmet and 3% MV. Median level of PTX3 was 21.7 (IQR: 13.5-58.23) ng/ml. In-hospital mortality was 25% (38 deaths); 13 patients (8.6%) underwent MV. PTX3 was associated with risk of death (per 10 ng/ml, HR 1.08; 95%CI 1.04-1.11; P<0.001) and death/MV (HR 1.04; 95%CI 1.01-1.07; P=0.011), independently of other predictors of in-hospital mortality, including age, Charlson Comorbidity Index, D-dimer and C-reactive protein (CRP). Patients with PTX3 levels above the optimal cut-off of 39.32 ng/ml had significantly higher mortality than the others (55% vs 8%, P<0.001). Higher PTX3 plasma levels were found in 14 patients with subsequent thrombotic complications (median [IQR]: 51.4 [24.6-94.4] versus 21 [13.4-55.2]; P=0.049). Conclusions High PTX3 levels in patients hospitalized with COVID-19 are associated with a worse outcome. The evaluation of this marker could be useful in prognostic stratification and identification of patients who could benefit from immunomodulant therapy.